Enhancing audit quality of Loans and advance to customers in small and medium commercial joint stock banks at Ernst $ Young Vietnam - Tran, Dieu Hong Anh (2020)
This research investigates about the audit procedures of loans and advance to customers section in financial audit at Ernst & Young Vietnam for commercial banks. Loans and advance is the survival unit of the bank, if this section does not properly work the bank itself may become bankrupt. Based on audit procedures, exploring about the strengths and limitations of the process. The research was conducted using qualitative approach. It began with observational and descriptive method to obtain procedures performed by EY Vietnam, according to EY GAM. In order to acquire indepth knowledge about the points that auditors should focus on when auditing loans and advance for commercial banks, the research used questionnaire designed for respondents, who are staff and seniors working at EY. Audit procedures were conducted at EY consist of 3 phases: Scope and Strategy phase, Execution phase and Conclusion phase. Finally, even there are some limitations, the process of auditing loans and advance to customers is standard and effective. This research also gives advices for further research and can be considered as the reference for the study and research purpose